Moralidade e cognição: um estudo com crianças de 7 e 10 anos em situação de risco social - Queiroz, Daiana Stursa de (2014)
This thesis aimwasto investigateand describe, undera psychogenic perspective, the relationshipbetween moral and cognitive aspects of children at social risk, based on the theory of Piaget. Participatingwere twentychildren, of both genders, between 7 and 10 years, goers a project, maintained by the municipal government, which works after school inVitória-ES, Brasil. Twotools were chosen, and applied in the following order: (1) Assessment Instrument of Moral Level Development (IANDM)and(2) Assessment Instrument of CognitiveLevelDevelopment (IANDC). Data analysis criteria were developed observing their quantity and quality, which established(1) the Response Levels to Item (NRI) for each of the eight items oftheinstruments; (2) the General Level of Moral Development (NGDM), (3) the General Level of Cognitive Development (NGDC).Results showed that with regard to IANDM it enables us toconfirm that most of the 7 year old children reached the IB level and most of the 10 yearold onesthe level IIA. Results showed that with regard to IANDC it enables us toconfirm that most of the children who are 7 years old reached the IB level and most of the 10 years the Level IIIA.Therefore,theprincipal results showedthat 10 year olds had higher levels when compared to 7 year olds, in bothinstruments. We concluded a broadening knowledge on the scope of social risk, through a unique methodology, and that IANDM and IANDC are essential tools in the diagnosis of Developmental Psychology.